The Role and Real Actions of Young Voters Post-2024 Simultaneous Elections - imran, imran; Ramadhani, Suci; Idharulhaq, Idharulhaq (Abdi Masyarakat, 2025)
This community service article examines the active role of young voters in North Lombok during and after the 2024 simultaneous elections, challenging prevailing narratives about youth political apathy. Based on participatory observation and discussion at the North Lombok Election Commission (KPU) podcast on November 28, 2025, this study documents how young people contributed significantly to electoral integrity through multiple roles including election organizers (KPPS and PPK), peace mediators, and sustained civic activists. The analysis employs the Sasak cultural philosophy of "Tioq, Tata, Tunaq" (cultivate, maintain, cherish) as a framework for understanding comprehensive democratic citizenship that extends beyond voting to include accountability monitoring and genuine commitment to national unity. Key findings reveal that youth political engagement flourishes when meaningful participation opportunities exist and when their contributions are recognized and valued. The article argues that addressing youth disengagement requires transforming political institutions rather than changing young people themselves, and calls for developing "good political will" among youth characterized by integrity, critical thinking, and public-regarding values to transform politics into a vehicle for collective progress. Recommendations include institutionalizing youth roles in electoral administration, strengthening civic education, creating formal mechanisms for youth policy input, and addressing structural barriers to participation. The North Lombok experience demonstrates that youth can be powerful democratic agents when properly engaged and supported.